Load-adaptive zero-phase-shift direct repetitive control for stand-alone four-leg VSI - Lidozzi, Alessandro; Solero, Luca; Crescimbini, Fabio; Ji, Chao; Zanchetta, Pericle (IEEE, 2016)
This paper deals with a dedicated load adaptive phase compensation algorithm to be used in Repetitive Control based stand-alone 4-leg VSI. The plant model is achieved, its inherent modifications according to the operating point are highlighted and used to properly adapt the Repetitive Control structure. Modification of the repetitive control parameters is described to obtain the desired phase compensation capabilities achieving a Zero-Phase-Shift condition at each harmonic. This allows to increase the gain of the Repetitive Controller at high order harmonics thus yielding a better VSI output voltages with strongly reduced THD and faster dynamic response. As a consequence, the VSI output voltages are almost independent from the loads to be fed and the 4-leg VSI with the proposed Zero-Phase-Shift Direct Repetitive Control is an ideal candidate to supply sensitive loads in microgrid, in particular for stand-alone applications.